Staphylococcus aureus is able to generate resistance to novel lipoglycopeptide antibiotic gausemycin A - Poshvina, Darya V.; Dilbaryan, Diana S.; Kasyanov, Sergey P.; Sadykova, Vera S.; Lapchinskaya, Olda A.; Rogozhin, Eugene A.; Vasilchenko, Alexey S. (Frontiers in Microbiology, 2022)
Gausemycin A is the first member of the novel lipoglycopeptides family produced by Streptomyces roseoflavus INA-Ac-5812. Gausemycin A has a pronounced bactericidal activity against methicillin-resistant Staphylococcus aureus. However, the ability of S. aureus to be resistant to gausemycin A has not been investigated yet. Using serial passaging, we have obtained the resistant variant S. aureus 5812R, which is 80 times more resistant compared to the parent strain. Susceptibility testing of S. aureus 5812R revealed the acquisition of cross-resistance to daptomycin, cefazolin, tetracycline, and gentamicin, while the resistance to vancomycin, nisin, and ramoplanin was absent. Whole genome sequencing revealed single nucleotide polymorphism (SNP) and deletions in S. aureus 5812R, among which are genes encoding efflux pump (sepA), the two-component Kdp system (kdpE), and the component of isoprenoid biosynthesis pathway (hepT). Phenotypically, S. aureus 5812R resembles a small-colony variant, as it is slow-growing, forms small colonies, and is deficient in pigments. Profiling of fatty acids (FA) composition constituting the cytoplasmic membrane of S. aureus 5812R revealed the prevalence of anteiso-branched FA, while straight FA was slightly less present. The evidence also showed that the gausemycin A-resistant strain has increased expression of the cls2 gene of the cardiolipin synthase. The performed checkerboard assay pointed out that the combination of gausemycin A and ciprofloxacin showed a synergistic effect against S. aureus 5812R.